Life and the nature of life - in parks - Rolston, Holmes, 1932-2025, author; Rowman and Littlefield Publishers, publisher (Colorado State University. Libraries, 2003)
Parks in the greater outdoors provide dimensions of depth belied by the recreational setting. A park is presence and symbol of the timeless natural givens. Humans realize within themselves something of the strength and goodness that nature has disciplined into its creatures. Parks put cultured humans in dialectic with spontaneous wild nature. In parks, we place boundaries and reserve sanctuaries where the nonhuman community of life is respected and can remain. Thereby we are uniquely human and our spirits are enriched.
A sourcebook for the Fifth World Parks Congress, International Union for Conservation of Nature (IUCN), Durban, South Africa, September 2003.
Keywords: nature conservation; protected areas; national parks and reserves; recreation; parks; philosophical places; nature